Factor affecting reading comprehension of Malaysian secondary school students - Vachiera, Jong Jut (2023)
Reading comprehension is the main method of integrating knowledge that promotes training methods and efficient coping in both academic and personal contexts. This research presents the factors affecting the reading comprehension of Malaysian secondary school students and how the affecting factors differ between the genders of the students. According to the findings, the majority of the students chose reading motivation affects the students’ reading comprehension. Even though, these students chose reading motivation as the factor that affects their reading comprehension, however, when it comes to the factor that affects them the most, the majority of the students chose vocabulary. Moreover, a strong correlation is found between reading motivation and vocabulary. Noting that the students chose these two factors, students' confidence in their capacity to read and comprehend texts may be impacted by their vocabulary. A strong vocabulary helps enhance reading motivation in students since it increases their sense of security when reading. From the findings obtained from the survey, it was revealed that the factors that affect reading comprehension do differ between the genders of the students. Even though most students chose similar factors, it can be seen that male students chose reading materials as the factor whereby none of the female students chose the factor. On the other hand, the female students, based on the findings obtained, revealed that reading without actually understanding it, the length of reading material provided was too long, and students lost interest in reading and the background knowledge affect their reading comprehension.